Depression and Perceived Social Support in the Elderly - Maryam Bakhtiyari; Mehregan Emaminaeini; Hossein Hatami; Soheila Khodakarim; Robab Sahaf (University of Social Welfare & Rehabilitation Sciences, 2017)
Objectives The purpose of the study was to determine depression and perceived social support and some related factors among the elderly people in urban areas of Tehran in the area of Shahid Beheshti University of Medical Sciences. Methods & Materials A cross-sectional study was conducted with 580 elderly of Tehran in Shahid Beheshti University using a multistage systematic sampling method. Data were collected by trained questioners. Standard Beck depression, Zimet perceived social support and demographic questionnaires were used. Analysis was performed by Stata software. Mann–Whitney test, Kruskal–Wallis test, Spearman correlation and descriptive tests were used in this study. Results The mean age of participants was 69.66 ± 7.91 years. A total of 67.53% of participants lived only with their spouses; 4.01% were illiterate and 89.69% owned at least one residential home. Health insurance coverage was for 92.38% of elderly. A total of 29.6 and 46.99% of the participants expressed their satisfaction with economic and living status, respectively. The prevalences of depression in mild, moderate and severe levels were 17.41%, 25.58%, and 8.88%, respectively, and it was 51.87% in average. A total of 72.38% of participants reported their agreement with perceived social support. Kruskal–Wallis test implied that the levels of depression had a significant relationship with perceived social support (P> 0.001). By a correlation test, a negative linear correlation was observed between depression and perceived social support (-0.388). The marital status, home ownership, health insurance, and of life and economic satisfaction showed a significant relationship with both perceived social support and depression variables. Education and depression were significantly related. But, gender and depression did not show any significant relationship. There was no significant relationship between gender and education with perceived social support. Conclusion Depression was found to be common in the elderly. There are similar economic and familial factors that are in relation to perceived social support and depression. According to the emotional and economic problems, creating the appropriate economic, cultural and social conditions can provide a healthier environment for the elderly to live in.